Osmolality and blood pressure stability during hemodialysis. Issue 6 (9th July 2017) - Singh, Anika T.; Mc Causland, Finnian R.
Abstract: Homeostatic regulation of plasma osmolality (POsm) is critical for normal cellular function in humans. Arginine vasopressin (AVP) is the major hormone responsible for the maintenance of POsm and acts to promote renal water retention in conditions of increased POsm. However, AVP also exerts pressor effects, and its release can be stimulated by the development of effective arterial blood volume depletion. Patients with end‐stage renal disease on hemodialysis, particularly those with minimal or no residual renal function, have impaired ability to regulate water retention in response to AVP. While hemodialysis can assist with this task, patients are subject to relatively rapid shifts in volume and electrolytes during the procedure. This can result in the development of transient osmotic gradients that lead to the movement of water from the extracellular to the intracellular space. Hypotension may result—both as a consequence of water movement out of the intravascular compartment, but also from impaired AVP release and inadequate vascular tone. In this review, we explore the evidence for POsm changes during hemodialysis, associations with adverse outcomes, and methods to minimize the rapidity of changes in POsm in an effort to reduce patient symptoms and minimize intra‐dialytic hypotension.